On the anvil - Lucado, Max. (Wheaton, Ill. : Tyndale House, 1985)
Stories on being.
Part Three: An instrument for noble purposes -- An instrument for noble purposes -- Today I will make a difference -- The tested tunnel -- The movement that was doomed to fail -- Communication is more than words -- Nonnegotiable love -- Singlehood: mistake or mission? -- The poison tongue -- The day of the question. The question! -- Five votes of confidence -- The wedding prayer -- Sarah -- The sonar fish finder -- Triumphant ... forever! -- The makings of a movement -- Conclusion: Emerging from the anvil -- Off the anvil.
Cover subtitle: Stories on being shaped into God's image.
Keywords: Christian life -- Meditations; Devotional literature